The Effects of Hyperbaric Oxygen Therapy in Treatment on Diverse Diseases - Maria Hermanowska; Julia Lubomirska; Aleksandra Brożyna; Anita Kwiatkowska; Arkadiusz Bydliński; Konrad Karłowicz; Natalia Małek; Sara Emerla; Patrycja Figurowska; Łukasz Ciulkiewicz (Nicolaus Copernicus University in Toruń, 2024)
INTRODUCTION: Hyperbaric oxygen therapy (HBOT) indeed holds significant therapeutic potential across various medical conditions, primarily by increasing the concentration of oxygen delivered to tissues under pressure. Saturating tissues with oxygen allows for the effective alleviation of underlying hypoxia, facilitating healing, tissue repair and mechanisms of action leads to reducing concentration of pro-inflammatory acute phase proteins, interleukins, and cytokines. Conversely, HBOT while also boosting levels of growth factors and other cytokines that promote angiogenesis. REVIEW METHODS: The article was complied by analyzing data from PubMed and Google Scholar regarding effects of hyperbaric therapy.  THE STATE OF KNOWLEDGE: Studies indicate that HBOT provides numerous opportunities in the treatment of extensive diseases acress various systems. Neurodegenerative disorders involve progressive nerve cell damage leading to motor or cognitive decline, exacerbated by oxidative stress and inflammation. HBOT has shown promise in delaying disease onset by improving mitochondrial dysfunction in motor neuron disease. In case of intestinal obstruction HBOT reduces intestinal gas volume, diameter of obstructed loops, and improves intestinal contractility. Significant benefits have been observed in conditions such as Crohn's disease and ulcerative colitis. Hyperbaric therapy presents potential benefits for the infertility, improving the environment for blastocyst implantation and pregnancy. CONCLUSION: There is no doubt that HBOT has a beneficial impact on treatment of many systems such as the nervous, cardiovascular, digestive, and skeletal. This innovative approach of hyperbaric therapy extends to selected disorders such as neurodegenerative diseases, Crohn's disease, ulcerative colitis, and infertility.